Molduras e enquadramentos: reflexões metodológicas para uma análise interacionista - Matheus Mazzilli Pereira (Ciências Sociais Unisinos)
This article aims to discus and connect the main methodological proposals developed by the interactionist perspective on framing applied to social movement studies. It is argued that two models were developed from distinct theoretical and conceptual assumptions: one focused on the analysis of internal mental cognitive structures and the other on the analysis of the meaning negotiation processes. The article proposed an alternative methodological model that connects these approaches. This model draws on theoretical insights developed by pragmatic sociological theories and by content and discourse analysis. The methodological proposal is illustrated with a research on the interactions between the animal rights movement and the mass media in Porto Alegre.